Mesenchymal stromal cells in tumor microenvironment remodeling of BCR-ABL negative myeloproliferative diseases - La Spina, Enrico; Giallongo, Sebastiano; Giallongo, Cesarina; Vicario, Nunzio; Duminuco, Andrea; Parenti, Rosalba; Giuffrida, Rosario; Longhitano, Lucia; Li Volti, Giovanni; Cambria, Daniela; Di Raimondo, Francesco; Musumeci, Giuseppe; et al. (Frontiers in Oncology, 2023)
Chronic myeloproliferative neoplasms encompass the BCR-ABL1-negative neoplasms polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF). These are characterized by calreticulin (CALR), myeloproliferative leukemia virus proto-oncogene (MPL) and the tyrosine kinase Janus kinase 2 (JAK2) mutations, eventually establishing a hyperinflammatory tumor microenvironment (TME). Several reports have come to describe how constitutive activation of JAK-STAT and NFκB signaling pathways lead to uncontrolled myeloproliferation and pro-inflammatory cytokines secretion. In such a highly oxidative TME, the balance between Hematopoietic Stem Cells (HSCs) and Mesenchymal Stromal Cells (MSCs) has a crucial role in MPN development. For this reason, we sought to review the current literature concerning the interplay between HSCs and MSCs. The latter have been reported to play an outstanding role in establishing of the typical bone marrow (BM) fibrotic TME as a consequence of the upregulation of different fibrosis-associated genes including PDGF- 𝛽 upon their exposure to the hyperoxidative TME characterizing MPNs. Therefore, MSCs might turn to be valuable candidates for niche-targeted targeting the synthesis of cytokines and oxidative stress in association with drugs eradicating the hematopoietic clone.